2019
DOI: 10.1186/s13075-019-1938-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disease-modifying anti-rheumatic drugs on bone structure and strength in psoriatic arthritis patients

Abstract: Objectives To address whether the use of methotrexate (MTX) and biological disease-modifying anti-rheumatic drugs (bDMARDs) impacts bone structure and biomechanical properties in patients with psoriatic arthritis (PsA). Methods This is a cross-sectional study in PsA patients receiving no DMARDs, MTX, or bDMARDs. Volumetric bone mineral densities (vBMDs), microstructural parameters, and biomechanical properties (stiffness/failure load) were determined by high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
0
20
0
2
Order By: Relevance
“…Compared to treatment naïve PsA patients, patients with a history of biological disease-modifying anti-rheumatic drugs (DMARD) treatment had significantly higher vBMD, BV/TV as well as greater trabecular number and thickness. No significant differences in bone density or microarchitecture outcomes were observed in patients previously treated with MTX compared to treatment naïve PsA patients ( 68 ).…”
Section: Pathologymentioning
confidence: 90%
“…Compared to treatment naïve PsA patients, patients with a history of biological disease-modifying anti-rheumatic drugs (DMARD) treatment had significantly higher vBMD, BV/TV as well as greater trabecular number and thickness. No significant differences in bone density or microarchitecture outcomes were observed in patients previously treated with MTX compared to treatment naïve PsA patients ( 68 ).…”
Section: Pathologymentioning
confidence: 90%
“…On the other hand, when human peripheral blood CD14 + monocytes are stimulated and cultured with monocyte colony stimulating factor and IL-17, osteoclasts differentiate in a concentration-dependent manner [23]. Recent studies have shown that the use of cytokine inhibitor improves BMD in PsA patients [24]. In our model, a large amount of inflammatory cytokines are produced from the skin lesions (manuscript in preparation); therefore, we tried to prevent osteoporosis using antibodies against inflammatory cytokines, such as TNF-α, IL-1α/β, and IL-17A/F, but BMD did not change in any of the groups (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…As concerning PsA, a recent study compared the effects of methotrexate (MTX) with bDMARDs on bone structure and biomechanical properties ( 125 ). It was found that bDMARD-treated patients had higher bone mass and better bone strength than patients receiving MTX or no DMARDs (despite longer disease duration in bDMARDs-treated group) ( 125 ).…”
Section: Psoriatic Arthritis and Spondyloarthritismentioning
confidence: 99%